2018
DOI: 10.1152/ajprenal.00112.2018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cannabidiol treatment on regulatory T-17 cells and neutrophil polarization in acute kidney injury

Abstract: Hallmark features of acute kidney injury (AKI) include mobilization of immune and inflammatory mechanisms culminating in tissue injury. Emerging information indicates heterogeneity of neutrophils with pro- and anti-inflammatory functions (N1 and N2, respectively). Also, regulatory T-17 (Treg17) cells curtail T helper 17 (Th-17)-mediated proinflammatory responses. However, the status of Treg17 cells and neutrophil phenotypes in AKI are not established. Furthermore, cannabidiol exerts immunoregulatory effects, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Flow Cytometry. Single-cell suspension was prepared for each mouse kidney and subjected to flow cytometry-based assays (Baban et al, 2009(Baban et al, , 2012(Baban et al, , 2018 to identify and analyze the numbers of total and subtypes of neutrophils and T cells as follows: neutrophils were initially identified as Ly-6G 1 /CD11b 1 cells and were presented as a percentage of whole kidney cells. Neutrophils were further identified as N1 (proinflammatory neutrophils) and N2 (regulatory neutrophils) using combinations of surface and intracellular markers, including Ly-6G 1 /CD11b 1 and tumor necrosis factor-a (TNF-a) for N1s and Ly-6G 1 /CD11b 1 /CD206 1 , and interleukin (IL)-10, for N2s.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Flow Cytometry. Single-cell suspension was prepared for each mouse kidney and subjected to flow cytometry-based assays (Baban et al, 2009(Baban et al, , 2012(Baban et al, , 2018 to identify and analyze the numbers of total and subtypes of neutrophils and T cells as follows: neutrophils were initially identified as Ly-6G 1 /CD11b 1 cells and were presented as a percentage of whole kidney cells. Neutrophils were further identified as N1 (proinflammatory neutrophils) and N2 (regulatory neutrophils) using combinations of surface and intracellular markers, including Ly-6G 1 /CD11b 1 and tumor necrosis factor-a (TNF-a) for N1s and Ly-6G 1 /CD11b 1 /CD206 1 , and interleukin (IL)-10, for N2s.…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of c m used the JC-1 assay, whereas apoptotic/ necrotic cell death in whole kidney cell preparations was determined using 7-aminoactinomycin D/caspase-3 assay as described previously (Baban et al, 2012(Baban et al, , 2018.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…86 A confirmation of in vivo induced Tregs by CBD was noted in an ischemia-reperfusion injury model in the kidney, in which CBD returned the disease-induced reduction in CD3 + Foxp3 + cells to baseline. 152 Interestingly, in the ischemia-reperfusion kidney model, CBD also induced ''TReg17 cells,'' which were defined as CD3 + Foxp3 + CCR6 + STAT3 + . 152 It has been suggested that Treg17 cells help control a TH17 response.…”
Section: Cbd Effects and Mechanisms Of Immune Suppression In Lymphocytesmentioning
confidence: 99%
“…152 Interestingly, in the ischemia-reperfusion kidney model, CBD also induced ''TReg17 cells,'' which were defined as CD3 + Foxp3 + CCR6 + STAT3 + . 152 It has been suggested that Treg17 cells help control a TH17 response. In vitro, CBD (5 lM) induced a CD69 + LAG + population in CD4 + CD25 À cells, which were identified as one type of regulatory cell, and induced Il10 mRNA expression.…”
Section: Cbd Effects and Mechanisms Of Immune Suppression In Lymphocytesmentioning
confidence: 99%